City brand and urban environmental sanitation: evidence from the national civilized city in China - Li, Junyan; Xu, Lei (Frontiers in Environmental Science, 2025)
IntroductionWith rapid urbanization and rising living standards, environmental sanitation management has emerged as a critical component of modern urban governance systems. Concurrently, urban brand has gained prominence as a key indicator of a city’s soft power in contemporary urban development studies.MethodsBased on panel data from 285 prefecture-level cities during 2001-2023, this study employs the acquisition of the National Civilized City (NCC) brand as a quasi-natural experiment and utilizes a difference-in-differences (DID) approach, with municipal solid waste collection and treatment as metrics for urban environmental sanitation, to investigate the impact and underlying mechanisms of city brand on environmental sanitation.ResultsThe findings reveal that: First, cities that achieved the NCC brand demonstrated significant improvements in environmental sanitation metrics, including increased municipal solid waste collection volume, harmless treatment volume, harmless treatment rate, and harmless treatment capacity. This improvement does not stem from short-term behaviors during the NCC evaluation period, but rather persists after obtaining the brand certification. Second, our mechanism analysis reveals that the NCC brand enhances urban environmental sanitation through three channels: improved sanitation infrastructure, increased governmental environmental attention, and heightened public environmental attention. Third, our heterogeneity analysis shows that the environmental impact varies across different urban contexts, with stronger effects observed in ordinary cities compared to higher-tier administrative centers, and more pronounced improvements in cities outside urban agglomerations versus those within urban agglomerations.DiscussionThis study broadens the research scope of city brand and enriches the environmental research framework within the Chinese context, while providing practical insights for policymakers seeking to enhance both city brand development and environmental management efficiency. The study proposes establishing long-term governance mechanisms combined with dynamic monitoring systems and adopting a multi-stakeholder co-governance model. Furthermore, it recommends implementing differentiated environmental strategies tailored to urban development levels.